Acute oral toxicity test and assessment of combined toxicity of cadmium and aflatoxin B1 in kunming mice. (September 2019) - Zhao, Qin; Yang, Zhao-Si; Cao, San-Jie; Chang, Yung-Fu; Cao, Yu-Qin; Li, Jia-Bing; Yao, Zi-Xuan; Wen, Yi-Ping; Huang, Xiao-Bo; Wu, Rui; Yan, Qi-Gui; Huang, Yong; et al.
Abstract: Cadmium and aflatoxin B1 (AFB1 ) are both common and widespread pollutants in food and feed. There are several reports on toxicity induced by Cadmium or AFB1 alone, but few address the toxicity caused by co-exposure to the two substances. In this study, 42 female and 42 male Kunming (KM) mice were divided into seven groups to test the acute oral toxicity of CdCl2 and AFB1, using Karber's method. The combined toxicity was assessed using the Keplinger evaluation system. Acute toxicity symptoms, deaths, and body and organ weights were evaluated, and hematological, blood biochemical, and histopathological analyses were conducted. The results revealed the following median lethal doses (LD50 ): LD50(Female KM mice)  = 62.56 mg/kg; LD50(Male KM mice)  = 48.79 mg/kg; LD50(KM mice) =55.27 mg/kg. The combined toxicity of AFB1 and CdCl2 showed an additive effect in mice, and an increase in the mixed dose of AFB1 and CdCl2 resulted in greater toxicity. These results demonstrated that the combined toxicity of AFB1 and CdCl2 was greater than the toxicities of the individual components in mice; thus, this may cause particular challenges when addressing these hazards in food and feed and the associated risk to human and animal health. Highlights: A toxicologic evaluation of co-exposure of Cd and AFB1 was conducted by combining food and feed relevant contaminants. Mixture toxicant LD50 values of CdCl2 and AFB1 in a KM mouse model were obtained from an equitoxic mixture ratio. AFB1 and CdCl2 produced an additive type of toxicity in mice. The effects of pathological changes in the target organs on mice were determined by co-exposure to CdCl2 and AFB1 .